Combining green and smart elements in a new idea of design of an ecological house - Demertzi, Melina; Gekas, Vassilis (My University, 2010)
Aim of this work is this paper is giving guidelines for the design of a house which combines the positive elements of both intelligent and green buildings, thereby it shows much better environmental- and also energy behavior. In the particular work there are presented all the theoretical elements which should be known as definitions for the comprehension of the results, in general, and also more concrete elements are given to distinguish the contribution of the two categories, namely the intelligent buildings and the green buildings. After having dealt with all the essential elements in the categories of buildings, the current thesis is completed with the design of the building. The external as well as the internal building characteristics will be chosen having in mind the climate condition of Greece. For easier understanding, specific examples (not hard guidelines) are given. Lastly, this paper exhibits the design of the building applying the AUTOCAD software, following the data and specification results given in the relevant diploma thesis of one of us, i.e. of Martha Demertzi[1].
Keywords: Environmental Engineering; AUTOCAD design; AutoCAD software; Building characteristics; Climate condition; Concrete elements; Ecological house; Essential elements; Green buildings; Intelligent designs; Smart elements; Ecology; Houses; Intelligent buildings; Systems science; Design